(untitled) (Islas, 2022)
Introduction: The present work makes an approach to the architecture of the Universidad Central «Marta Abreu» de Las Villas, exponent of a moment where in Cuba the design was developed under the codes of the Modern Movement and the significant participation of local and recently formed architects. Methods: A bibliographic review and the analysis of documents have been used to study the work of the main architects and their participation in the project of the Universidad Central «Marta Abreu» de Las Villas. Results: We start by presenting the memory of the project conceived by the authors of the team that designed the university to make a tour of the architecture of the complex and the other work they produced as part of their creative work. Other architects who were also involved in the completion of the campus on the eve of its 70th anniversary are also mentioned. Conclusions: The university project was developed under the codes of the architecture of the Modern Movement and the Miesian influence of university campuses. Although only a part of the initial complex was built, after the triumph of the revolution it was expanded with new concepts and construction technologies but respecting its urban conception with buildings inserted in abundant green spaces. The initial work is the result of a creative work that is complemented by other buildings of its authors in various themes with a predominance of housing.